Comparative Efficacy of Anti-TNF Therapies For The Prevention of Postoperative Recurrence of Crohn's Disease: A Systematic Review and Network Meta-Analysis of Prospective Trials. Issue 6 (July 2019) - Bakouny, Ziad; Yared, Fares; El Rassy, Elie; Jabbour, Rita; Hallit, Rachel; Khoury, Nathalie; Honein, Khalil; Bou Jaoude, Joseph
Abstract : Introduction: There is a lack of studies on the optimal anti–tumor necrosis factor (anti-TNF) agent for postoperative prophylaxis of Crohn's disease (CD) recurrence. Therefore, we conducted a network meta-analysis (NMA) of prospective trials to compare the efficacy of anti-TNF agents in the prevention of postoperative endoscopic and clinical recurrence of CD following ileocolonic resection. Methods: We searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and recent American gastroenterology association (AGA) meeting abstracts through August 2017. We selected prospective studies comparing anti-TNF agents among each other or to other agents in the setting of postoperative prevention of CD recurrence. We performed a NMA using a frequentist approach with generalized pairwise modeling and inverse variance heterogeneity method. Results: We identified 9 studies, including 571 patients and 5 treatment agents, among which 2 anti-TNF drugs (adalimumab and infliximab). Compared with infliximab, our NMA yielded the following results for endoscopic recurrence: adalimumab [odds ratio (OR), 0.92; 95% confidence interval (CI), 0.18-4.75], thiopurines (OR, 4.11; 95% CI, 0.68-24.78), placebo (OR, 4.39; 95% CI, 0.70-27.68), and Mesalamine (OR, 37.84; 95% CI, 3.77-379.42). For clinical recurrence: adalimumab (OR, 1.03; 95% CI, 0.17-6.03), thiopurines (OR, 1.40; 95% CI, 0.20-10.02), placebo (OR, 1.77; 95% CI, 1.01-3.10), and mesalamine (OR, 16.54; 95% CI, 1.55-176.24). Conclusions: On the basis of a NMA combining direct and indirect evidence either adalimumab or infliximab may be used in the postoperative prophylaxis of CD recurrence. There is currently a lack of evidence on the use of other anti-TNF agents in this setting. Abstract : Supplemental Digital Content is available in the text.